Detection and Quantitation of DNA Damage on a Genome‐wide Scale Using RADAR‐seq. Issue 11 (14th November 2022) - Zatopek, Kelly M.; Potapov, Vladimir; Ong, Jennifer L.; Gardner, Andrew F.
Abstract: The formation and persistence of DNA damage can impact biological processes such as DNA replication and transcription. To maintain genome stability and integrity, organisms rely on robust DNA damage repair pathways. Techniques to detect and locate DNA damage sites across a genome enable an understanding of the consequences of DNA damage as well as how damage is repaired, which can have key diagnostic and therapeutic implications. Importantly, advancements in technology have enabled the development of high‐throughput sequencing‐based DNA damage detection methods. These methods require DNA enrichment or amplification steps that limit the ability to quantitate the DNA damage sites. Further, each of these methods is typically tailored to detect only a specific type of damage. RAre DAmage and Repair (RADAR) sequencing is a DNA sequencing workflow that overcomes these limitations and enables detection and quantitation of DNA damage sites in any organism on a genome‐wide scale. RADAR‐seq works by replacing DNA damage sites with a patch of modified bases that can be directly detected by Pacific Biosciences Single‐Molecule Real Time sequencing. Here, we present three protocols that enable detection of thymine dimers and ribonucleotides in bacterial and archaeal genomes. Basic Protocol 1 enables construction of a reference genome required for RADAR‐seq analyses. Basic Protocol 2 describes how to locate, quantitate, and compare thymine dimer levels in Escherichia coli exposed to varying amounts of UV light. Basic Protocol 3 describes how to locate, quantitate, and compare ribonucleotide levels in wild‐type and ΔRNaseH2 Thermococcus kodakarensis . Importantly, all three protocols provide in‐depth steps for data analysis. Together they serve as proof‐of‐principle experiments that will allow users to adapt the protocols to locate and quantitate a wide variety of DNA damage sites in any organism. © 2022 New England Biolabs. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : Constructing a reference genome utilizing SMRT sequencing Basic Protocol 2 : Mapping and quantitating genomic thymine dimer formation in untreated versus UV‐irradiated E. coli using RADAR‐seq Basic Protocol 3 : Mapping and quantitating genomic ribonucleotide incorporation in wildtype versus ΔRNaseH2 T. kodakarensis using RADAR‐seq